Sytuacja na globalnym rynku ubezpieczeń w latach 2003-2006 - Bera, Anna (Global Insurance Market between 2003 and 2006, 2008)
The world insurance market is strongly connected with the global economy. Economic growth and capital markets boom influenced the financial performance of the insurance companies. Information, presented in the article, concerning the world insurance market shows, that the fastest growing insurance market is the market of life insurances. Non-life insurance market noted quite moderate growth during the period analyzed. Emerging markets are more dynamic in the volume of insurance premium than industrialized countries. In the next future, these markets will be penetrated by the world biggest insurance companies which expect the further fast increase in the volume of insurance premium.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 39-49